Population genetic structure of Asiatic Hard Clam (Meretrix meretrix) in Thailand based on Cytochrome Oxidase subunit I gene sequence - VERAKIAT SUPMEE; PRADIT SANGTHONG; APIRAK SONGRAK; JUTHAMAS SUPPAPAN (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Supmee V, Sangthong P, Songrak A, Suppapan J. 2020. Population genetic structure of Asiatic Hard Clam (Meretrix meretrix) in Thailand based on Cytochrome Oxidase subunit I gene sequence. Biodiversitas 21: 2702-2709. The Asiatic hard clam (Meretrix meretrix) is an important commercial clam in Thailand. Last decade, this species had a dramatic decrease. Thus, to conserve this species, genetic information is essential. In our study, 135 samples of M. meretrix were collected from 7 sampling sites along the Thailand coast. The genetic structure was examined based on the variation of the nucleotide sequence in cytochrome oxidase subunit I gene. Twenty haplotypes were identified. Numerous rare haplotypes were revealed indicating the existence of a large female effective population size.  In the northern Gulf of Thailand population, the genetic diversity was low. The neutrality test and minimum spanning network showed experienced expansion events of M. meretrix in Thailand. The genetic structure showed that the M. meretrix population was separated into the Gulf of Thailand and the Andaman population. This finding was possibly caused by a disruption of gene flow from the Thai-Malay Peninsula and larval behavior. Our finding suggested that the construction management program to maintain the genetic diversity of this species could be separated into 2 conservation units.